Fragments of Local Identity in Fiction Films Shot in the Region of Bío-Bío, Chile (2020)
The main objective of the research discussed in this paper was to identify fragments of the Bío-Bío (Chile) region, which are present in fiction films shot in the area between 2010 and 2017. At a specific level, the aim was to study the contribution of cinema in the construction of local identity, as well as hierarchize the identity traits detected in the filmic sample. Through the selected methodology, the cinematographic production of the region was identified, and then possible identity traits that could characterize the local community in a certain period of time were studied. For this purpose, the content of the analyzed films was taken into consideration, a group interview and individual interviews were carried out with expert sources and key informants, respectively, and findings were contrasted with a documentary study that gave a context view at a local level. In turn, identity theory was used to give epistemic support to the challenge posed in the research’s objectives. Finally, the presence or absence of identity traits in the film sample was analyzed through direct observation and analysis of characters and environments, and the postulates of apparent and latent content. Among the most important findings, it is worth noting that the most recurrent identity traits in the cinema analyzed were natural catastrophes, followed by the indigenous and peasant traits. On the other hand, it was determined that most of the films do possess many of the identitary features identified and co-constructed in the area. Therefore, it can be concluded that in the analyzed time period, the cinema of the Bío-Bío region contributed to the construction of a local identity through the inclusion of specific identity fragments, which were explicit in the films.